2011
DOI: 10.1080/02705060.2011.582696
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and salinity on growth ofThalassiosira pseudonana(Bacillariophyceae) isolated from ballast water

Abstract: We examined the impacts of environmental factors on the survival of ballast water-introduced planktonic organisms and specifically described the effects of temperature and salinity on growth of the centric diatom Thalassiosira pseudonana. In salinity gradient experiments for natural phytoplankton communities of the vessel Daewoo Diamond, several freshwater and marine species were successfully identified. Of these, T. pseudonana was the dominant species in all salinity conditions (2-30 psu). In combination expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 13 publications
3
10
0
3
Order By: Relevance
“…pseudonana attained a maximum growth rate at 20–25 °C (Fig. S3 , SI), which is consistent with results of studies with other organisms 10 , 30 . Upper thermal limit for growth of T .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…pseudonana attained a maximum growth rate at 20–25 °C (Fig. S3 , SI), which is consistent with results of studies with other organisms 10 , 30 . Upper thermal limit for growth of T .…”
Section: Discussionsupporting
confidence: 90%
“…Comparatively, as shown in this study, growth of diatoms was more affected by temperature than by salinity. Temperature is a dominant accessory factor controlling the growth of aquatic organisms, such as microalgae, fish and cladocerans 10 , 30 , 42 , 43 . In this study, 96-h IC50s of ZnO-NPs for T .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T . pseudonana has been shown to grow at a wide range of salinities and temperatures [52], and to have anaerobic capabilities [53].…”
Section: Discussionmentioning
confidence: 99%
“…For example, salinity level has been shown to affect the spatial distribution of benthic diatoms by modifying their migratory behavior or favoring a drifting strategy (Underwood et al ., ; Sauer et al ., ; Araujo et al ., ). Field and laboratory experiments have also shown that salinity alone or in combination with other physicochemical factors can impact diatom growth (Baek et al ., ; Sogaard et al ., ) and cell size (De Miranda et al ., ), induce changes in photosynthesis and primary production (Radchenko and Il'iash, ; Osborn and Hook, ), elicit oxidative stress responses (Rijstenbil, ; Zhang et al ., ) and induce changes in the morphology of the diatoms' silica shell (frustules; Vrieling et al ., ; Martin‐Cereceda and Cox, ; Trobajo et al ., ; Ligowski et al ., ; Leterme et al ., ). Variation in salinity level can also influence the production of dimethylsulfoniopropionate (Lyon et al ., ; Kettles et al ., ), a biogenic precursor of a climatically active sulfur compound that is involved in cloud formation.…”
Section: Introductionmentioning
confidence: 98%